Notary Liability in Criminal Acts of Fraud Based on a Power of Buying Deed - Panduwinata, Poppy Agustina; Purwadi, Hary; Novianto, Widodo Tresno (Journal of World Science, 2022)
The aims of this study are as follows: a) To find out the violations committed by the notary in this case fulfill the elements of a criminal act of fraud as in determining Article 378 of the Criminal Code regarding fraud; b) To find out the basis for the consideration of the reviewing judge (PK) in deciding that the case is in accordance with the duties and authorities of a notary as regulated in the Law on Notary Positions. The method used in this research is the doctrinal method (doctrinal research) with secondary data sources. That the facts of the trial of Decision Number 20 PK/Pid/2020 state that the notary commits a criminal act of fraud as referred to in Article 378 of the Criminal Code does not meet the following elements: a) The objective element (element of the act committed) and b) Subjective element (element of intent or purpose). ) which consists of benefiting personally or others and violating the law. The judge in his consideration stated that there was negligence of the Defendant in the process of making the power of attorney for the deed of sale and purchase between the witnesses, then the settlement was administratively. Freeing a notary based on the fraudulent sale and purchase deed according to legal facts, regarding the loss of victim witness Marhendro Anton Inggriyono who was harmed by witness Gunawan Priambodo who did not perform his/her obligations or defaults, it turned out that the Defendant was being processed by criminal law, even though according to the facts of the trial, he did not receive any profit from the transaction of making a power of attorney deed of sale and purchase of land at Paradise Loft.